Desenvolvimento radicular e aéreo, nutrição e eficiência de absorção de macronutrientes e zinco por cultivares de arroz de terras altas afetadas pela adubação fosfatada - Costa Crusciol, Carlos Alexandre [UNESP]; Nascente, Adriano Stephan; Mauad, Munir; Lima Silva, Ana Claudia de [UNESP] (Universidade Estadual de Londrina (UEL), 2013)
In Brazil, phosphorus availability is one factor that that more limit yield of upland rice under rainfed system. Then, better understanding of cultivars development at phosphorus soil fertilization is very important in the production systems making this more sustainable. The objective was to evaluate the influence of phosphorus doses applied to the soil over the root length, root and shoot dry matter, concentration and content of macronutrient and zinc in shoot and root as well as the efficiency of nutrient uptake per meter root of upland cultivars of intermediate and modern groups. The experiment was carried out in greenhouse conditions in a completely randomized design in factorial scheme 4 x 4. Treatments were four levels of P fertilization applied at the soil (0, 50, 100 and 200 mg dm(-3) of P) and four upland rice cultivars (Maravilha - modern group, IAC-201, IAC-202 and Carajas - intermediate group). There is increase in phosphorus availability in the soil with increasing levels of P fertilization. Under low phosphorus availability, cultivars of the intermediate group have better shoots and root system development in relation to the modern cultivar group. Level of phosphorus affected nutrients contents in shoots and root system of upland rice cultivars. The increasing phosphorus fertilization increased uptake of nutrients per meter of root; and although under higher phosphorus availability there was a greater root growth, in low phosphorus availability root growth was greater at the expense of shoot growth.
Root and shoot development, nutrition and uptake efficiency of macronutrients and zinc by upland rice cultivars as affected by phosphorus fertilization
Keywords: Oryza sativa L.; nutrients; root; plant growing in pots